Gender-Related Association of Serum Uric Acid Levels with Premature Ventricular Contraction - Yin, Xiaomeng; Yang, Xiaolei; Xia, Yunlong; Wang, Binhao; Wu, Shouling; Chen, Yue; Khalid, Bin Waleed; Li, Wenyu; Lv, Haichen (International Heart Journal, 2018)
In this study, we aim to investigate the association of serum uric acid (SUA) with the prevalence of premature ventricular contraction (PVC). The relationship between SUA and the prevalence of PVC in 98,965 subjects (79,034 male subjects, mean age: 51.9 ± 12.6 years old) in the Kailuan cohort study (n = 101,510, age range: 18-98 years) from June 2006 to October 2007 was investigated. These subjects were divided into five groups on the basis of their SUA levels. A multivariate logistic regression model was constructed to evaluate the association between SUA and the prevalence of PVC. The prevalence of PVC was 1.1% in all subjects, 1.1% in male subjects, and 1.0% in female subjects. Compared with the first quintile of SUA, the odds ratio (OR) and 95% confidence interval (95% CI) of other quintiles were 1.33 (1.05-1.69), 1.14 (0.90-1.46), 1.37 (1.08-1.74), and 1.63 (1.30-2.06) in male subjects; 1.12 (0.68-1.87), 1.27 (0.77-2.09), 1.45 (0.90-2.36), and 1.33 (0.81-2.18) in female subjects; and 1.30 (1.04-1.61), 1.20 (0.96-1.50), 1.33 (1.07-1.66), and 1.57 (1.26-1.95) for all subjects. The correlation between SUA and the prevalence of PVC was significant in all subjects and in male subjects, but not in female subjects. We demonstrated that SUA was apparently associated with the prevalence of PVC. The significant relationship between SUA and PVC identified in male subjects suggests the potential involvement of a gender-specific mechanism. Prospective studies are needed to further corroborate our results.